Filicinae Taxonomic Diversity in the Tourism Area of Tretes Waterfall Wonosalam Kabupaten Jombang - Nuraini, Afifah Mei; Wisanti, Wisanti (Universitas Negeri Surabaya, 2022)
Filicinae is a fern with the most species members. The Filicinae includes approximately 170 genera and 7000 species. Filicinae grows in wet, humid, and shady environmental conditions, like waterfall areas with an altitude of 1100-1300 meters above sea level (m a s l). The study aimed to determine the taxonomic diversity of the Filicinae in the Tretes Wonosalam Waterfall Tourism area. Taxonomic diversity is very important in tourism areas because it prevents species extinction due to the destruction of the habitat, they live in. This was descriptive research with exploration and observation techniques used purposive sampling methods based on altitude. The results of the study were stated in the form of an inventory list of species and families of each station. Data gained of species diversity were analyzed using taxonomic diversity with the formula (?) and dominance diversity with the formula (?*). Exploration results found 37 species from 12 families composed of 10 species from 7 families at station 1; 12 species from 6 families at station 2; 14 species from 7 families at station 3; and 22 species from 12 families at station 4. The highest taxonomic diversity (?) was station 4 with 106.8 while the lowest for station 1 was 25.63. Dominance diversity (?*) at all stations in this study was in the medium category. The highest family found in the study was Tectariaceae with six species.